2023
DOI: 10.1021/acs.jpcc.2c07619
|View full text |Cite
|
Sign up to set email alerts
|

Selective Conversion of the CaO-Captured CO2 to CH4 by Ni- and Hydrogen-Assisted Calcium Looping Processes in a Batch Reactor

Abstract: Storing and hydrogenating CO 2 to CH 4 is an efficient solution to alleviate the greenhouse effect and energy shortage. This work demonstrated that the CaO-captured CO 2 could be selectively converted to CH 4 by Ni-and hydrogenassisted calcium looping (CaL) processes in a batch reactor. The Ni/CaO composite was first synthesized in one step at room temperature by calcium-induced hydrogenation of Ni-mixed calcium carbonate without the use of any solvent and CO 2 emission. The CO 2 capture properties over the Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…S2b,† the Ni/CaO composites were greenly prepared by Ca and Ni-induced mechanochemical hydrogenation of CaCO 3 , as reported in our previous work. 35 Then, the Ni/CaO/γ-Al 2 O 3 composites were obtained by ball milling Ni/CaO with γ-Al 2 O 3 at low speed (200 rpm). The obtained solid material was analyzed by XRD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2b,† the Ni/CaO composites were greenly prepared by Ca and Ni-induced mechanochemical hydrogenation of CaCO 3 , as reported in our previous work. 35 Then, the Ni/CaO/γ-Al 2 O 3 composites were obtained by ball milling Ni/CaO with γ-Al 2 O 3 at low speed (200 rpm). The obtained solid material was analyzed by XRD.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that CO 2 can be captured and selectively converted to CH 4 over the Ni/CaO composite through an energy-saving calcium looping (CaL) process at moderate temperatures (450–550 °C) under static pressure conditions. 35 The CO 2 capture capacity and the CH 4 yield for hydrogenating over the 50Ni/2–1CaO composite reach 0.33 mmol g −1 and 68.58%, respectively. This method is fit for small-scale CO 2 conversion.…”
Section: Introductionmentioning
confidence: 92%